2016
DOI: 10.15517/rgac.v54i0.23281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ashes from the 2014-2015 Turrialba Volcano eruptions by means of Scanning Electron Microscopy and Energy Dispersive X-Ray Spectroscopy

Abstract: El volcán Turrialba es un estratovolcán localizado aproximadamente 35 km al noroeste de San José, la ciudad capital de Costa Rica. Desde el 29 de octubre de 2014, hasta al menos el fin del año 2015, el volcán mostró una serie de erupciones que representan su actividad más significativa desde la década de los 1860s. Estas erupciones dispersaron un volumen significativo de cenizas, las cuales alcanzaron las áreas más pobladas del país. En este artículo, se analizan las características de las partículas de ceniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Similarly, Lücke and Calderón (2016) reported analyses from recent Turrialba ash surfaces with high silica and low alkali content, which probably do not reflect true magmatic compositions. Rather, our analyses provide strong geochemical evidence indicating juvenile magma interaction with hydrothermal fluids, supporting a phreatomagmatic eruption mechanisms.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, Lücke and Calderón (2016) reported analyses from recent Turrialba ash surfaces with high silica and low alkali content, which probably do not reflect true magmatic compositions. Rather, our analyses provide strong geochemical evidence indicating juvenile magma interaction with hydrothermal fluids, supporting a phreatomagmatic eruption mechanisms.…”
Section: Resultsmentioning
confidence: 96%
“…Such material could be due to the reworking or erosion of tephra from the walls of the conduit and active crater, as has been observed in other ashes and similar cases (Mastin, 1991;Suzuki et al, 2013;and references cited therein). Lücke and Calderón (2016) use scanning electron microscopy (SEM) and energy disperse X-ray spectroscopy for analyzing the ash from 2014 to 2015 under the fraction 2.7 phi fraction (fine ash), and they concluded that the 2014 eruption was phreatic because they concluded that the ashes were composed entirely of non-juvenile fragments, and only the 2015 eruption was phreatomagmatic. Alvarado et al (2016) conclude that the 2014 eruption was instead phreatomagmatic based on the presence of hydratation cracks, and describe in Spanish the current eruption in detail, the tephra deposits, including granulometric and Xray diffraction analyses, petrography and mineralogy, and applied the sequential fragmentation/transport theory.…”
Section: Previous Work Of Clast Components At Turrialba Current Eruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monitoring network of RSN (UCR and ICE) is detailed in Table 1. RSN contains a laboratory of geochemistry and a laboratory of petrology for aqueous and rock samples, that together with other laboratories at University of Costa Rica, makes RSN able to carry out specific research [Lücke and Calderón 2016]. Gravity measurement campaigns are conducted by RSN for specific research at volcanoes [Argüello et al 2019].…”
Section: Recent Volcanic Activitymentioning
confidence: 99%
“…Turrialba started with phreatic activity in 2010, and since 2015, juvenile magma has been involved in the eruptions (Lücke and Calderón, 2016). Meanwhile, the volcanic activity at Poás started in April 2017 with a phreatomagmatic eruption, which led to the closure of the national park (one of the most visited national parks in Central America) and impacting the daily lives of people near the volcano (Ruiz and Suárez, 2017).…”
Section: Sites Of Studymentioning
confidence: 99%